Decentralization and Human Resource Quality Drive Inventory Control Efficiency: Desentralisasi dan Kualitas Sumber Daya Manusia Mendorong Efisiensi Pengendalian Persediaan - Pranata, Paksi Rahmat; Arizanda Rahayu, Ruci (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the influence of audit committee variables, decentralization, and human resource competence on internal inventory control implementation at Surya Mart. Conducted through quantitative methods and surveying 32 employees and stakeholders, the research finds that decentralization and human resource quality positively impact internal control effectiveness, while the audit committee variable shows no significant influence. The results emphasize the importance of organizational factors in shaping internal control practices in small-scale enterprises like Surya Mart, offering insights for managerial decision-making and highlighting avenues for future research to expand understanding in this area. Highlights: 1. Quantitative investigation examines organizational factors on inventory control at Surya Mart.2. Decentralization positively influences internal control, enhancing operational efficiency.3. Future research: explore variables, methodologies to advance small-scale enterprise inventory management. Keywords: Internal inventory control, Organizational factors, Small-scale enterprises, Audit committee, Human resource competence